Weaving threads between intersectionality, agency, and capabilities in sociological theory - Souza, Marcio Ferreira de (2021)
The critique produced by feminist thought had relevant contributions to social studies by emphasizing how the gender category can assist in understanding the social world. More recently, the intersectional approach to feminism has demonstrated how gender, linked to other categories such as race, class, sexuality, generation, and locality, can assist in more complex analyses of social phenomena. In this article our goal is to mobilize the intersectional approach to review the notions of agency and capabilities, aiming to offer an analytical sociological contribution on the constitution of autonomous subjects. To do so, we highlight contributions from the intersectional approach and then rework the notions of agency and capabilities, weaving combinations between the founders of these concepts with representatives of the intersectional approach.